Experimental Test of Compressive Strength of Concrete by Using Wastewater Tofu - Muh. Sayfullah. S (Civil Engineering Faculty, Universitas Muhammadiyah Buton, 2022)
Tofu waste is one type of waste produced by many people in Indonesia because the type of tofu food is the easiest to get. This study used tofu wastewater as a substitute for water and as a concrete treatment with certain changes in cement water components. Tofu water waste is waste that comes from wasted soybean treatment residues that cannot be consumed and the result of this tofu water waste is usually only disposed of. The purpose in this study is to determine the compressive strength value of concrete using tofu waste water and treatment using tofu wastewater. In the implementation using laboratory experimental methods. From the results of the compressive strength test showing the lower compressive strength value of concrete using wastewater tofu obtained a higher compressive strength value compared to using normal water PDAM. The compressive strength value using tofu water is 71.80 kg / cm² at the age of 7 days, 92.30 kg / cm² at the age of 7 days, 119.10 kg / cm² at the age of 7 days 28 days and the compressive strength value of concrete using normal water PDAM Baubau City is 46.30 kg/cm² at the age of 3 days, 59.20 kg/cm² at the age of 7 days and 88.00 kg/cm² at the age of 28 days.